Praktik Pinjol Ilegal dan Fenomena Jaminan Foto Vulgar di Minahasa Selatan (Studi Literatur) - Kezia Roslaura N. Moniung (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
Loan activities or debts and receivables are common in Indonesian people in the scope of daily life. This research is intended to delve into the criminal law related to lending activities by focusing on regulations and phenomena that often occur along with the impact on users. This research uses data collection methods from various relevant sources or literature studies. The findings of this study prove that regulations and user rights are often ignored in credit lending activities and online loans (pinjol) or illegal loan funds. In this study, it is to voice more affirmations of civil law and criminal law against aggrieved users. The results of the study examined the factors, characteristics and impacts from various sides on illegal online loan users and on the perpetrators of these illegal online loans. This research yielded results regarding the low level of public literacy in social media which drags users to participate in online lending activities and activities with an attractive appearance and a fast process without further identifying the risks in the future